2009
DOI: 10.1007/s10439-009-9794-y
|View full text |Cite
|
Sign up to set email alerts
|

Wall Shear Stress and Pressure Distribution on Aneurysms and Infundibulae in the Posterior Communicating Artery Bifurcation

Abstract: A growing number of cases of rupture at an infundibulum, progression of infundibulum to a frank aneurysm, and subarachnoid hemorrhage (SAH) in the posterior communicating artery (PCoA) have been reported. Using patient-specific geometric models of the supraclinoid internal carotid artery (ICA) with PCoA infundibulum or aneurysm, high-resolution computational fluid dynamics simulations were performed by solving the Navier-Stokes equations with a spectral/hp element method. Simulation results show that the flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 54 publications
2
23
0
1
Order By: Relevance
“…As previously reported by Chien et al 6 and Baek et al, 27 aneurysm and vascular shape affect pulsatile flow properties at the aneurysm site. These effects are made especially clear when a single, standard flow profile is used for hemodynamic analysis of all cases, as is the standard method and was done in this research.…”
Section: Discussionsupporting
confidence: 56%
“…As previously reported by Chien et al 6 and Baek et al, 27 aneurysm and vascular shape affect pulsatile flow properties at the aneurysm site. These effects are made especially clear when a single, standard flow profile is used for hemodynamic analysis of all cases, as is the standard method and was done in this research.…”
Section: Discussionsupporting
confidence: 56%
“…5,33 Computer simulations provide a relatively straightforward way to explore the effect of geometry on flow characteristics, such as wall shear stress (WSS). Although computer simulations can predict the fluid dynamics in anatomically realistic in vitro models, 3 assumptions are inevitably made in such models. For example, assuming rigid vessel walls and Newtonian flow, 2,32 which may not be sufficiently physiologically realistic, requires that validation with in vivo data should be conducted wherever possible.…”
Section: Introductionmentioning
confidence: 99%
“…This approach was considered because we found that the ID of the PCo-A had a wide junction with the internal carotid artery, making full clipping quite difficult similar to wide-necked aneurysms [21]. Moreover, a previous study has shown that the bleeding points in the ruptured ID of the PCo-A were mostly located at the distal side of the ID, close to the internal carotid artery [22]. Under such circumstances, blood could still flow into the inside of the ID along the PCo-A even when the origin of the ID is clipped.…”
Section: Discussionmentioning
confidence: 99%